DESAIN PENGENDALI PI PADA PWM RECTIFIER TIGA FASA DALAM MEREDUKSI THD - Joeken King Abednego Judianto; Mochammad Rusli; Tri Nurwati (Jurnal Mahasiswa TEUB, 2022)
This paper investigates on the design of proportional-integral (PI) controller with three-phase pulse-width modulation (PWM) rectifier as the plant to be controlled. PWM rectifier is used to reduce the total harmonic distortion (THD) injected to the system from nonlinear load used. Space vector pulse-width modulation technique is used to control the switching of the rectifier where three-phase currents and voltages are presented in the synchronous reference frame. Vector control strategy is used to carry out the modulation for optimal DC voltage output and THD reduction. In order to have optimally designed controller, gain parameters based on cascade-control of the voltage and current controller are tuned based on symmetrical optimum and modulus optimum tuning method. Simulation using MATLAB/Simulink are done to verify the stability of the output DC voltage and reduction of the THD. Three-phase voltage sources use 220 Volt input supply and obtained stable 600 Volt DC output and reduced THD of 1.80%.Keywords: PWM rectifier, vector control, total harmonic distortion, PI controller, symmetrical o